Optimization of Cocoa Bean Husk Fiber Delignification Using Marasmius sp. via Solid-State Fermentation - Mita Ramadiyanti; Rachmat Adiputra; Triana Ulfah; Melia Siti Ajijah; Raden Duhita Diantiparamudita Utama; Hari Hariadi (Postgraduate, University of Mataram, 2026)
Cocoa bean shell fiber is an abundant lignocellulosic by-product from the cocoa agroindustry with high cellulose potential but limited utilization due to its lignin content. This study aimed to optimize the delignification of cocoa bean shell fiber using Marasmius sp through solid state fermentation (SSF) as an environmentally friendly approach to obtain cellulose-rich fibers as precursors for agro-industrial applications. Delignification was evaluated under various fermentation parameters, including pH (4–6), glucose concentration (2–5 g/L), temperature (27–37°C), and incubation time (7–14 days). Lignin content was determined using the Van Soest method, while fiber morphology was observed using Scanning Electron Microscopy (SEM). The optimum SSF conditions were achieved at pH 5, glucose concentration of 5 g/L, temperature of 32°C, and incubation time of 14 days, resulting in lignin reduction of 70.29% ± SD without significant damage to the cellulose structure. These results indicate that SSF using Marasmius sp is an effective and sustainable delignification strategy to produce cellulose-rich fibers suitable as nanocellulose precursors for agricultural and agro-industrial materials.